POLA KOMUNIKASI VERBAL DAN NONVERBAL DALAM KEGIATAN BELAJAR MENGAJAR ANTARA GURU DAN MURID SMP TIPE B DI SLB NEGERI KABUPATEN KARAWANG - dede miftahur; Fajar Hariyanto (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2025)
This study aims to explore and describe the patterns of verbal and nonverbal communication between teachers and B-type students (deaf) at the junior high school level at SLB Negeri Kabupaten Karawang in teaching and learning activities. Using a descriptive qualitative approach and in-depth interviews with two teachers as informants, the study illustrates how communication within the learning process is shaped and adapted to accommodate students’ hearing limitations. The findings reveal that teachers implement various communication patterns, including linear (one-way), interactive (two-way), multilateral (group), and total communication (komtal). These patterns are adjusted based on the students’ conditions, abilities, and needs. Nonverbal communication, such as gestures, facial expressions, body movements, and visual media, plays a crucial role in effectively conveying messages. Total communication is the primary approach as it integrates multiple communication modes to comprehensively meet students’ needs. The findings emphasize the importance of teachers’ adaptability and empathy in building effective social interaction with deaf students.